2013
DOI: 10.1007/978-3-642-25643-1_2
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Across the Air-Sea Interface

Abstract: The efficiency of transfer of gases and particles across the air-sea interface is controlled by several physical, biological and chemical processes in the atmosphere and water which are described here (including waves, large-and small-scale turbulence, bubbles, sea spray, rain and surface films). For a deeper understanding of relevant transport mechanisms, several models have been developed, ranging from conceptual models to numerical models. Most frequently the transfer is described by various functional depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 350 publications
(505 reference statements)
0
95
0
Order By: Relevance
“…For instance, Weiss et al (2007), Prytherch et al (2010) and Edson et al (2011) used the eddy covariance method while Ho et al (2011) used the tracer method to determine k empirically. These two methods have their relative advantages (see e.g., Garbe et al, 2014, for a review) but it has been shown that k measured by the eddy covariance method leads to higher values than other methods (e.g., Jacobs et al, 2002). The only empirical formulation of k that could eventually be applied globally is that of Ho et al (2011) due to the variety of data used for calibration.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Weiss et al (2007), Prytherch et al (2010) and Edson et al (2011) used the eddy covariance method while Ho et al (2011) used the tracer method to determine k empirically. These two methods have their relative advantages (see e.g., Garbe et al, 2014, for a review) but it has been shown that k measured by the eddy covariance method leads to higher values than other methods (e.g., Jacobs et al, 2002). The only empirical formulation of k that could eventually be applied globally is that of Ho et al (2011) due to the variety of data used for calibration.…”
Section: Discussionmentioning
confidence: 99%
“…Though some major biogeochemical principles are known, detailed dynamical formulations of processes are scarce and in their infancy. There is a considerable uncertainty about the gas transfer velocity of CO 2 and other gases across the air-water interface (Carpenter et al, 2012;Garbe et al, 2014). While the global ocean carbon sink estimates may not too strongly depend on this choice (otherwise projections with simple two box models for the global ocean would not have worked at all; Oeschger et al, 1975), the projected local CO 2 concentration in ocean surface waters is highly influenced by the chosen gas transfer velocity values, also for appropriate regional validation of ocean models.…”
Section: Process and Impact Knowledgementioning
confidence: 99%
“…A detailed overview of all of these processes and their interactions is given by Wanninkhof et al (2009) and Garbe et al (2014). Many of the processes shown in figure 5 can either be directly monitored from satellite remote-sensing (e.g.…”
Section: Atmosphere-ocean Gas Fluxesmentioning
confidence: 99%